Wild bonobos experience unusually low bone resorption during early lactation relative to humans and other mammals - Behringer, Verena; Sonnweber, Ruth; Fruth, Barbara; Housman, Genevieve; Douglas, Pamela Heidi; Stevens, Jeroen M. G.; Hohmann, Gottfried; Kivell, Tracy L. (Evolutionary Human Sciences)
In mammals, pregnancy and lactation are marked by calcium stress and bone resorption, leading to reduced bone mineral density. In humans, these periods may partly explain the higher prevalence of osteoporosis in older women compared with men, but lactation patterns in modern humans may reflect cultural influences rather than natural conditions. The extent to which these findings apply to wild-living mammals remains unknown. We measured urinary C-terminal crosslinking telopeptide of Type I collagen (CTX-I) levels, a bone resorption marker, during pregnancy in wild and zoo-housed bonobos (Pan paniscus) and during lactation in wild bonobos. Studying wild-living primates such as bonobos can provide insights into ancestral reproductive adaptations. We found an increase in CTX-I levels towards the end of pregnancy in zoo-housed and primiparous wild females. Contrary to expectations, CTX-I levels during early lactation are lower than in other reproductive phases. This pattern diverges from the assumption that lactation increases bone resorption. Our findings suggest that wild bonobos may use physiological or behavioral strategies to modulate bone metabolism during lactation. These adaptations, shaped in natural environments, provide insight into evolutionary pressures on skeletal health and may inform strategies to mitigate bone loss in humans.
Keywords: Reproductive phase; Hominoid; CTX-I; Bone turnover markers; Pan paniscus; Bone density

Lydia Böttger (Universität Paderborn) rezensiert: Burwitz-Melzer, Eva; Riemer, Claudia; Schmelter, Lars (Hrsg.) (2022): Feedback beim Lehren und Lernen von Fremd- und Zweitsprachen. Arbeitspapiere der 42. Frühjahrs- konferenz zur Erforschung des Fremdsprachenunterrichts. [Giessener Beiträge zur Fremdsprachendidaktik]. Tübingen: Narr Francke Attempto, 245 Seiten. ISBN 978-3- 8233-8569-1 - Böttger, Lydia (www.daz-portal.de)

Mentoring-Programm zur Einarbeitung neuer Lehrbeauftragter. Format, Inhalte und Evaluationsergebnisse. - Behrent, Sigrid (Sprachen. Politik. Sprachenpolitik. Der Beitrag der Sprachenzentren zur Hochschule der Zukunft. Dokumentation der 31. Arbeitstagung vom 5.-7. März 2020 an der Europa-Universität Viadrina in Frankfurt (Oder))

Lydia Böttger (Universität Paderborn) rezensiert: Michalak, Magdalena; Döll, Marion (Hrsg.) (2021): Lehrwerke und Lehrmaterialien im Kontext des Deutschen als Zweitsprache und der sprachlichen Bildung. [Deutsch als Zweitsprache Positionen, Perspektiven, Potenziale, Bd. 2]. Münster, New York: Waxmann, 164 Seiten. ISBN 978-3-8309-4105-7. - Böttger, Lydia (www.daz-portal.de)

Schreibberatung im Kontext beruflicher Bildung und ihre Auswirkung auf Emotionen beim Schreiben - Dohmann, Olga; Drumm, Sandra; Niederhaus, Constanze (Zur sprachlichen und gesellschaftlichen Integration neu zugewanderter Menschen. Eine Bilanz.)

Ein universitäres DaF-Unterrichtsprojekt im Spiegel von Curriculumdiskussion und berufsbezogenem Fremdsprachenunterricht - Prikoszovits, Matthias (Informationen Deutsch als Fremdsprache)
Zusammenfassung Im Beitrag wird zunächst erläutert, wie sich Curriculumforschung und berufsbezogenes Lernen und Lehren im Bereich Deutsch als Fremdsprache seit den 1990er Jahren entwickelt haben, um in einem weiteren Schritt zu beschreiben, wie sich ein konkretes Unterrichtsprojekt in die DaF-Curriculumdiskussion eingliedert. Dabei wird vor allem auf die Frage eingegangen, ob die Forderung nach einer Berufsorientierung im universitären Fremdsprachenunterricht mit dem Unterrichtsprojekt umgesetzt wurde. Untersuchungsgegenstand ist eine im Jahr 2014 an der Germanistik der University of St Andrews (Schottland, GB) durchgeführte, benotete Projektarbeit, bei der Studierende des vierten und letzten Studienjahres Werbeclips drehen mussten.
Keywords: General Medicine

Mixed messages: wild female bonobos show high variability in the timing of ovulation in relation to sexual swelling patterns - Douglas, Pamela Heidi; Hohmann, Gottfried; Murtagh, Róisín; Thiessen-Bock, Robyn; Deschner, Tobias (BMC Evolutionary Biology)
Background: The evolution of primate sexual swellings and their influence on mating strategies have captivated the interest of biologists for over a century. Across the primate order, variability in the timing of ovulation with respect to females’ sexual swelling patterns differs greatly. Since sexual swellings typically function as signals of female fecundity, the temporal relation between ovulation and sexual swellings can impact the ability of males to pinpoint ovulation and thereby affect male mating strategies. Here, we used endocrine parameters to detect ovulation and examined the temporal relation between the maximum swelling phase (MSP) and ovulation in wild female bonobos (Pan paniscus). Data were collected at the Luikotale field site, Democratic Republic of Congo, spanning 36 months. Observational data from 13 females were used to characterise female swelling cycles (N = 70). Furthermore, we measured urinary oestrone and pregnanediol using liquid chromatography–tandem mass spectrometry, and used pregnanediol to determine the timing of ovulation in 34 cycles (N = 9 females). Results: We found that the duration of females’ MSP was highly variable, ranging from 1 to 31 days. Timing of ovulation varied considerably in relation to the onset of the MSP, resulting in a very low day-specific probability of ovulation and fecundity across female cycles. Ovulation occurred during the MSP in only 52.9 % of the analysed swelling cycles, and females showed regular sexual swelling patterns in N = 8 swelling cycles where ovulation did not occur. These findings reveal that sexual swellings of bonobos are less reliable indicators of ovulation compared to other species of primates. Conclusions: Female bonobos show unusual variability in the duration of the MSP and in the timing of ovulation relative to the sexual swelling signal. These data are important for understanding the evolution of sexual signals, how they influence male and female mating strategies, and how decoupling visual signals of fecundity from the periovulatory period may affect intersexual conflict. By prolonging the period during which males would need to mate guard females to ascertain paternity, the temporal variability of this signal may constrain mate-guarding efforts by male bonobos.
Keywords: Primate; Sexual signalling; Fecundity; Endocrine analysis; LC–MS/MS; Estrogen; Pan paniscus; Pregnanediol; Mate guarding

The Steady State Great Ape? Long Term Isotopic Records Reveal the Effects of Season, Social Rank and Reproductive Status on Bonobo Feeding Behavior - Oelze, Vicky M.; Douglas, Pamela Heidi; Stephens, Colleen R.; Surbeck, Martin; Behringer, Verena; Richards, Michael P.; Fruth, Barbara; Hohmann, Gottfried (PLOS ONE)
Dietary ecology of extant great apes is known to respond to environmental conditions such as climate and food availability, but also to vary depending on social status and life history characteristics. Bonobos (Pan paniscus) live under comparatively steady ecological conditions in the evergreen rainforests of the Congo Basin. Bonobos are an ideal species for investigating influences of sociodemographic and physiological factors, such as female reproductive status, on diet. We investigate the long term dietary pattern in wild but fully habituated bonobos by stable isotope analysis in hair and integrating a variety of long-term sociodemographic information obtained through observations. We analyzed carbon and nitrogen stable isotopes in 432 hair sections obtained from 101 non-invasively collected hair samples. These samples represented the dietary behavior of 23 adult bonobos from 2008 through 2010. By including isotope and crude protein data from plants we could establish an isotope baseline and interpret the results of several general linear mixed models using the predictors climate, sex, social rank, reproductive state of females, adult age and age of infants. We found that low canopy foliage is a useful isotopic tracer for tropical rainforest settings, and consumption of terrestrial herbs best explains the temporal isotope patterns we found in carbon isotope values of bonobo hair. Only the diet of male bonobos was affected by social rank, with lower nitrogen isotope values in low-ranking young males. Female isotope values mainly differed between different stages of reproduction (cycling, pregnancy, lactation). These isotopic differences appear to be related to changes in dietary preference during pregnancy (high protein diet) and lactation (high energy diet), which allow to compensate for different nutritional needs during maternal investment.

A novel approach for dominance assessment in gregarious species: ADAGIO - Douglas, Pamela Heidi; Ngonga Ngomo, Axel-Cyrille; Hohmann, Gottfried (Animal Behaviour)
The concept of social dominance has been used in a plethora of studies to assess animal behaviour and relationships between individuals for nearly a century. Nevertheless, a standard approach does not yet exist to assess dominance in species that have a nonlinear or weakly linear hierarchical structure. We amassed 316 published data sets and show that 73.7% of the data sets and 90.3% of 103 species that we reviewed do not have a strongly linear structure. Herein, we present a novel method, ADAGIO, for assessing the structure of dominance networks. ADAGIO computes dominance hierarchies, in the form of directed acyclic graphs, to represent the dominance relations of a given group of animals. Thus far, most methods for computing dominance ranks assume implicitly that the dominance relation is a total order of the individuals in a group. ADAGIO does not assume or require this to be always true, and is hence more appropriate for analysing dominance hierarchies that are not strongly linear. We evaluated our approach against other frequently used methods, I&SI, David's score and Elo-rating, on 12 000 simulated data sets and on 279 interaction matrices from published, empirical data. The results from the simulated data show that ADAGIO achieves a significantly smaller error, and hence performs better when assigning ranks than other methods. Additionally, ADAGIO generated accurate dominance hierarchies for empirical data sets with a high index of linearity. Hence, our findings suggest that ADAGIO is currently the most reliable method to assess social dominance in gregarious animals living in groups of any size. Furthermore, since ADAGIO was designed to be generic, its applicability has the potential to extend beyond dominance data. The source code of our algorithm and all simulations used for this paper are publicly available at http://ngonga.github.io/adagio/.
Keywords: aggression; behaviour; comparability; directed acyclic graph; hierarchy; linearity; nonlinearity; social rank; totality

Female sociality during the daytime birth of a wild bonobo at Luikotale, Democratic Republic of the Congo - Douglas, Pamela Heidi (Primates)
Parturition is one of the most important yet least observed events in studies of primate life history and reproduction. Here, I report the first documented observation of a bonobo (Pan paniscus) birth event in the wild, at the Luikotale Bonobo Project field site, Democratic Republic of the Congo. The nulliparous mother’s behaviour before, during and after parturition is described, along with reactions of other community members to the birth and the neonate. Data were collected through focal-animal observations, and the events postpartum were photo-documented. The behaviour and spatial distribution of party members were recorded using scan samples. Parturition occurred during the late morning in a social context, with parous females in close proximity to the parturient mother. Placentophagia occurred immediately after delivery, and the parturient shared the placenta with two of the attending females. I compare this observation with reports of parturition in captive bonobos, and highlight the observed female sociality and social support during the birth event. Plausible adaptive advantages of parturition occurring in a social context are discussed, and accrued observations of birth events in wild and free-ranging primates suggest that females may give birth within proximity of others more frequently than previously thought. This account contributes rare empirical data for examining the interface between female sociality and parturition, and the evolution of parturitional behaviours in primates.
Keywords: Birth; Pan paniscus; Parturition; Perinatal behaviour; Placentophagia; Female sociality

Lifelong Learning - auch für Lehrkräfte?! Angebote zur Fort- und Weiterbildung an Sprachenzentren - Behrent, Sigrid; Lorenz, Gunter (Excellent und initiativ. Qualitätsentwicklung und -sicherung in der Sprachausbildung an Hochschulen. Dokumentation der 26. Arbeitstagung 2010.)

La communication interalloglotte. Communiquer dans la langue cible commune. - Behrent, Sigrid